1993
DOI: 10.1364/ol.18.001795
|View full text |Cite
|
Sign up to set email alerts
|

Steering of optical beams in nonlinear Kerr media by spatial phase modulation

Abstract: A simple scheme to steer optical beams is proposed. The basic idea is to impose a sinusoidal phase modulation on the optical beam and then propagate it in a nonlinear Kerr medium. Spatial phase modulation splits the input beam into multiple subbeams, while the nonlinear medium shapes a particular subbeam into a spatial soliton in such a way that most of the beam power appears in a narrow beam whose direction can be controlled by changing the modulation parameters. We present numerical results showing how spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…6 At the same time sinusoidal modulation permits closed-form evaluation of the integrals appearing in Eq. (12) and inequality (14), resulting in simple expressions for the steering angle and the soliton condition.…”
Section: B Analytical Results For Sinusoidal Phase Modulationmentioning
confidence: 99%
See 4 more Smart Citations
“…6 At the same time sinusoidal modulation permits closed-form evaluation of the integrals appearing in Eq. (12) and inequality (14), resulting in simple expressions for the steering angle and the soliton condition.…”
Section: B Analytical Results For Sinusoidal Phase Modulationmentioning
confidence: 99%
“…4 Another technique uses the properties of dark solitons for beam steering. 5 Recently Ryan and Agrawal 6 proposed a new technique that employs spatial phase modulation of a beam entering a nonlinear media, and they showed that high-efficiency beam steering is possible. In their method spatial phase modulation splits the input beam into many subbeams while the nonlinear medium shapes a particular subbeam into a spatial soliton in such a way that most of the power appears in a narrow beam whose direction can be controlled by changes in the modulation parameters.…”
Section: --mentioning
confidence: 99%
See 3 more Smart Citations